Biopolítica e democracia em Giorgio Agamben - Duarte, Fábio Henrique (Universidade Federal de Santa Catarina, 2019)
This work aims to problematize the democracy as an essential political regime in our contemporary culture, with theoretical support of biopolitics. Firstly, a general characterization of democracy, with its main elements, highlighting the democratic State of Law was done. In order to justify the research, secondly, it is desired to make an exposition of the biopolitics based on Michel Foucault’s theory, later, its redefinition in the work of Giorgio Agamben was made. After applying the way of understanding the biopolitics through the Italian thinker, an approach to economics and democracy was explicited. At the end, after exposing how democracy can be reflected from biopolitics, it is argued that by relying on Agamben's ideas, one can perceive the limitations of democracy understanding that the critique of this political regime is one of the inexcusable tasks of the contemporary political philosophy.